(untitled) (World Bulletin of Public Health, 2025)
This scientific article explores the significance of leveraging digital platforms to enhance the methodological support for developing the cognitive competencies of future teachers. In an era characterized by rapid technological advancements, integrating digital tools into teacher education programs has become imperative. By utilizing digital platforms effectively, teacher training can be enriched with interactive learning experiences, personalized instruction, and innovative teaching methods. This article delves into the benefits, challenges, and best practices associated with utilizing digital platforms to foster the cognitive development of aspiring educators.